Gram-Scale Synthesis of Blue-Emitting CH3NH3PbBr3 Quantum Dots Through Phase Transfer Strategy - Zhang, Feng; Xiao, Changtao; Li, Yunfei; Zhang, Xin; Tang, Jialun; Chang, Shuai; Pei, Qibing; Zhong, Haizheng (Frontiers in Chemistry, 2018)
Reprecipitation synthesis has been demonstrated to be a simple and convenient route to fabricate high quality perovskite quantum dots toward display applications, whereas the limited chemical yields (<10%) and difficulty of purification limited its further application. In order to overcome this issue, we here report a modified emulsion synthesis by introducing phase transfer strategy, which achieving effective extraction of newly formed perovskite quantum dots into non-polar solvent and avoiding the degradation of perovskite quantum dots to a large extent. Based on this strategy, gram-scale CH3NH3PbBr3 quantum dots were fabricated in 10 mL (~ 0.02 mol/L) colloidal solution with chemical yields larger than 70%. The as fabricated CH3NH3PbBr3 quantum dots exhibit an emission peak of 453 nm and a full width at half maximum of only 14 nm. Moreover, electroluminescent devices based on blue emitting CH3NH3PbBr3 quantum dots were also explored with a maximum luminance of 32 cd/m2, showing potential applications in blue light emitting devices.